Probation Officer Productivity: Using the Effort-Reward Imbalance Model - Presley, Brandon (2017)
The purpose of this study is to determine the extent to which workplace efforts and rewards are associated with probation officer stress, overcommitment, health, and productivity. This research uses the effort-reward imbalance model, which is an indicator of job stress, on a group of criminal justice probation officers. The probation officers completed questionnaires regarding their perceptions of health, perceived reward, perceived effort, perceptions of overcommitment, and perceived productivity. Afterward, the responses were collected, and analyses were conducted using correlation and multiple regression to determine the extent to which perceptions of effort, reward, and overcommitment effect probation officer productivity and health. A sample of 207 probation officers from Central Florida selected probation agencies are used in the study, with an individual response rate of approximately 90%. The results suggest that perceptions of reward have a limited effect on perceived productivity. Furthermore, the study found a significant relationship between effort-reward imbalance and perceptions of overcommitment. The study also found a significant relationship between perceptions of overcommitment and perceptions of reduced health. Finally, the study found that the interaction of effort-reward imbalance and overcommitment are correlated with negative perceptions of health. The results of the study demonstrate the ubiquity of perceptions among probation officers that they are overworked and under compensated. The results also suggest the need for improvements in organizational practice, so that efficiency and effectiveness of probation officers can be maximized